2021
DOI: 10.3390/plants10081522
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Reproduction Is More Advantageous Than Sexual Reproduction in a Canopy-Forming Clonal Macroalga under Ocean Warming Accompanied by Oligotrophication and Intensive Herbivory

Abstract: Ocean warming and the associated changes in fish herbivory have caused polarward distributional shifts in the majority of canopy-forming macroalgae that are dominant in temperate Japan, but have little effect on the alga Sargassum fusiforme. The regeneration ability of new shoots from holdfasts in this species may be advantageous in highly grazed environments. However, little is known about the factors regulating this in Sargassum species. Moreover, holdfast tolerance to high-temperature and nutrient-poor cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…This indicates that although yak grazing activated the K. humilis shoot pool and improved the grazing tolerance of K. humilis (Wang et al, 2017), it did not stimulate further development of shoots into nutrient branches. Many studies have shown that increase investment in sexual reproduction decreases investment in vegetative reproduction, suggesting that there is a significant trade-off between sexual and vegetative reproduction (Wang et al, 2018;Liu, 2020;Endo et al, 2021). Our results support this suggestion.…”
Section: Effects Of Grazing Treatments On Reproductive and Life Histo...supporting
confidence: 88%
“…This indicates that although yak grazing activated the K. humilis shoot pool and improved the grazing tolerance of K. humilis (Wang et al, 2017), it did not stimulate further development of shoots into nutrient branches. Many studies have shown that increase investment in sexual reproduction decreases investment in vegetative reproduction, suggesting that there is a significant trade-off between sexual and vegetative reproduction (Wang et al, 2018;Liu, 2020;Endo et al, 2021). Our results support this suggestion.…”
Section: Effects Of Grazing Treatments On Reproductive and Life Histo...supporting
confidence: 88%
“…Clearly, more studies are needed to examine if populations that have a different genetic history, environmental history, and acclimation methodology show a different response to stress (e.g. Macrocystis pyrifera (Linnaeus) C. Agardh; Laminariales;Fern andez et al 2020Fern andez et al , 2021. Furthermore, in the present study, we did not elucidate the mechanism that details how desiccation reduces photochemical efficiency; however, elucidating this mechanism is essential for this species in future studies for a better understanding of why this species can flourish in such an extreme environment.…”
Section: Discussionmentioning
confidence: 99%
“…holdfast and new shoots) to survive a summer‐time environment (Endo et al . 2021). Likewise, according to our past study that reported the effects of temperature and irradiance characteristics on photosynthesis, which includes the diurnal change of photochemical efficiency in the natural state by using optical dissolved oxygenic sensors and pulse amplitude modulation (PAM)‐chlorophyll fluorometry (Kokubu et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endo et al [26] demonstrate a high tolerance of holdfasts (the equivalent of roots in seaweeds, which anchor the organism to the sea floor) to heat stress in the brown alga Sargassum fusiforrme. Under high temperature and low nutrition conditions, holdfasts can grow and regenerate into new shoots by vegetative reproduction, i.e., asexual reproduction.…”
mentioning
confidence: 99%